Specific function of vitamin D in bone - Dennisa Putri Ramadhani; Hammanda AD; Salsabila Azzahra; Akbar Rizkyadsyah; Anis Ulayya; Miftahul Huda Fendiyanto (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2024)
There are two sources of vitamin D, namely from food and sun exposure. The content of vitamin D is given beneficial in bone and mineral metabolism. Vitamin D helps absorption of calcium in the intestines, thereby accelerating bone mineralization. Bone metabolism is a complex process that occurs throughout life. Very high doses of vitamin D can stimulate an increased rate of bone loss. Vitamin D deficiency causes bone demineralization. Which can cause a decrease in calcium absorption. The functions of these metabolites vary widely in vital metabolic pathways. This review aims to determine the specific function of vitamin D in bone. The search for the data base was carried out by the analytical method. Vitamin D which is absorbed from food or comes from the skin turns into an active form in the form of 1,25- (OH) 2-D3 which will enter the bloodstream, playing an important role in bone and extra-skeletal health.